Faktor Yang Mempengaruhi Rendahnya Cakupan K4 - Darmayanti, Ika; Rohmatin, Homsiatur (MIDWIFERY JOURNAL, 2023)
Background: The K4 examination assists in monitoring the health of pregnant mothers regularly during the pregnancy period, ensuring that the health conditions of both the mother and the fetus progress well. One of the primary objectives of the K4 examination is to monitor the growth and development of the fetus. This examination helps ensure that the fetus is developing properly and maintains optimal health. Through the K4 examination, pregnant mothers can receive education, information, and counseling regarding proper pregnancy care, balanced nutrition, labor preparation, as well as postnatal care. This study aims of this study is to determine the factors influencing the low coverage of K4 in the working area of Ajung Primary Health Center. Method This study employed a quantitative research design with a descriptive correlational approach using a cross-sectional method. The population consisted of 35 respondents selected through total sampling technique. The analysis used the Chi-Square test. The research findings showed that the majority of respondents belonged to the multipara category, with 29 respondents (58%). Half of them had an income of 1 million to 2 million, totaling 25 respondents (50%). Most respondents had good knowledge, accounting for 38 respondents (76%). The majority also had good family support, with 34 respondents (68%), and most respondents achieved the target coverage of visits, totaling 39 respondents (78%). The results of the chi-square test analysis indicated a value of α<0.05, namely (0.000), for each independent variable (parity, economy, knowledge, and family support), leading to the conclusion that there is a correlation between the factors influencing the low coverage of K4 in the working area of Ajung Primary Health Center. These implications can serve as a basis for developing interventions involving various sectors, such as economic empowerment, improved accessibility to healthcare services, and increased family involvement in supporting K4. Keywords: family support, K4 coverage, economy, parity and knowleage ABSTRAK Latar belakang Pemeriksaan K4 membantu dalam pemantauan kesehatan ibu hamil secara teratur selama masa kehamilan, memastikan bahwa kondisi kesehatan ibu dan janin berjalan dengan baik. Salah satu tujuan utama pemeriksaan K4 adalah untuk memantau pertumbuhan dan perkembangan janin. Pemeriksaan ini membantu memastikan bahwa janin berkembang dengan baik dan memiliki kesehatan yang optimal. Melalui pemeriksaan K4, ibu hamil dapat menerima edukasi, informasi, dan konseling tentang perawatan kehamilan yang benar, nutrisi yang seimbang, persiapan persalinan, serta perawatan pasca persalinan. Tujuan penelitian ini untuk mengetahui Faktor faktor yang mempengaruhi rendahnya cakupan K4 di wilayah kerja Puskesmas Ajung. Metode Penelitian ini merupakan penelitian kuantitatif, desain penelitian digunakan diskriptif korelasi dengan pendekatan cross sectional. Dengan jumlah populasi sebanyak 35 responden dengan tenik sampling total Sampling. Dan uji analisis yang digunakan menggunakan Chi- Square test. Dari hasil penelitian didapatkan sebagian besar responden memiliki parietas kategori multipara sebanyak 29 responden (58%), Separuh memiliki penghasilan 1juta-2juta sebanyak 25 responden (50%), Sebagian besar memiliki pengetahuan kategori baik sebanyak 38 responden (76%), Sebagian besar memiliki dukungan keluarga kategori baik sebanyak 34 responden (68%), Dan sebagian besar responden d memiliki cakupan kunjungan kategori tercapai sebanyak 39 responden (78%).Hasil uji analisis chi-square tets menunjukkan nilai α<0,05, yaitu ( 0,000) untuk setiap variabel bebas (parietas, ekonimi, pengetahuan dan dukungan keluarga) sehingga dapat disimpulkan ada Hubungan Faktor faktor yang mempengaruhi rendahnya cakupan K4 di wilayah kerja Puskesmas Ajung. Saran Implikasi ini dapat menjadi dasar untuk mengembangkan intervensi yang melibatkan berbagai sektor, seperti pemberdayaan ekonomi, peningkatan aksesibilitas layanan kesehatan, dan peningkatan peran serta keluarga dalam mendukung K4. Kata kunci: dukungan keluarga, cakupan K4, ekonomi, parietas dan pengetahuan,